Mechanisms of oxidative stress, apoptosis, and autophagy involved in graphene oxide nanomaterial anti-osteosarcoma effect - Tang Z (Dove Medical Press, 2018)
Zhibing Tang,1,2,* Lin Zhao,1,3,* Zaixing Yang,3 Zhaohui Liu,4 Jia Gu,3 Bing Bai,3 Jinlian Liu,2 Jiaying Xu,3 Huilin Yang1 1Department of Orthopedics, The First Affiliated Hospital of Soochow University, Soochow University, Suzhou, China; 2Department of Orthopaedic Surgery, Suzhou Kowloon Hospital, Shanghai Jiaotong University School of Medicine, Suzhou, China; 3Institute of Quantitative Biology and Medicine, SRMP and RAD-X, Collaborative Innovation Center of Radiation Medicine of Jiangsu Higher Education Institutions, Soochow University, Suzhou, China; 4Department of Anatomy and Histology and Embryology, Basic Medical and Biological Sciences, School of Medicine, Soochow University, Suzhou, China *These authors contributed equally to this work Background: Graphene and its derivative graphene oxide (GO) have been implicated in a wide range of anticancer effects. Purpose: The objective of this study was to systematically evaluate the toxicity and underlying mechanisms of GO on two osteosarcoma (OSA) cancer cell lines, MG-63 and K7M2 cells. Methods: MG-63 and K7M2 cells were treated by GO (0-50 µg/mL) for various time periods. Cell viability was tested by MTT and Live/Dead assays. A ROS Detection Kit based on DHE oxidative reaction was used for ROS detection. An Annexin V-FITC Apoptosis Kit was used for apoptosis detection. Dansylcadaverine (MDC) dyeing was applied for seeking unspecific autophagosomes. Western blot and Immunofluorescence analysis were used for related protein expression and location.Results: K7M2 cells were more sensitive to GO compared with MG-63 cells. The mechanism was attributed to the different extent of the generation of reactive oxygen species (ROS). In K7M2 cells, ROS was easily stimulated and the apoptosis pathway was subsequently activated, accompanied by elevated expression of proapoptosis proteins (such as caspase-3) and decreased expression levels of antiapoptosis proteins (such as Bcl-2). A ROS inhibitor (N-acetylcysteine) could alleviate the cytotoxic effects of GO in K7M2 cells. However, the production of ROS in MG-63 cells was probably inhibited by the activation of an antioxidative factor, nuclear factor-E2-related factor-2, which translocated from the cytoplasm to the nucleus after GO treatment, while a nuclear factor-E2-related factor-2 inhibitor (ML385) significantly increased ROS production in MG-63 cells when combined with GO treatment. In addition, autophagy was simultaneously stimulated by characteristic autophagosome formation, autophagy flux, and increased the expression level of autophagy-related proteins (such as LC3I to LC3II conversion, ATG5, and ATG7). Conclusion: This paper proposes various underlying mechanisms of the anticancer effect of GO. The novel synthetic use of GO with an oxidizing agent is the key step for further potential applications in clinical OSA cancer therapy. Keywords: graphene oxide, osteosarcoma cancer, ROS, apoptosis, autophagy